Analysis on the mechanism and dynamics of frequent debris flows in typical alpine gorges areas—a case study of Yizhong river in Deqin County, Yunnan, China - Wang, Yan; He, Qing; Wang, Wenpei; Zhang, Nan; Chen, Liang; Liu, Zhen; Chen, Dian; Yang, Lin (Frontiers in Earth Science, 2024)
Debris flow is a common geological disaster in mountainous areas, which occurs frequently in the rainy season and has strong mobility and destructiveness, often bringing serious loss of life and property. Previous studies have focused more on single outbreaks of debris flow disasters, and less on multiple outbreaks of debris flow disasters in the same gully during the rainy season, which makes it more difficult to carry out prevention and control work for similar disasters. Because the occurrence of the disaster has its corresponding geomechanical model as the basis, which provides the necessary scientific basis for the prevention and control of the disaster.Through data collection, field investigation, drone aerial photography, modelling and rainfall data analysis, the geological environment of Yizhong River Basin and the frequent occurrence mechanism of debris flow disasters were investigated, and a conjugate shear-type disaster-inducing geomechanical model was proposed. With the help of RAMMS numerical simulation software, the dynamic mechanism of the disaster threatening the life and property safety of the residents in Deqin County was analysed to provide the necessary scientific basis for the prevention and control of the Yizhong River debris flow disaster. Base on the characteristics of the geological environment in alpine and gorge areas, the necessity and advantage of applying the nap-of-the-object photogrammetry technology to engineering geological survey in alpine and gorge areas are put forward.